2011
DOI: 10.1159/000330683
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Complications of Acute Intermittent Porphyria

Abstract: Background: Acute intermittent porphyria (AIP) is an inherited disorder of heme biosynthesis, the clinical manifestations of which are incompletely understood. In this report, we describe 12 cases of AIP, focusing on the neurological manifestations. Methods: Twelve patients were diagnosed with AIP on the basis of characteristic clinical findings, erythrocyte porphobilinogen deaminase (PBGD) activity, and molecular genetics. Central and peripheral nervous system manifestations were noted, and electrophysiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 29 publications
2
34
0
1
Order By: Relevance
“…However, a PBGD‐deficient mouse model of AIP neuropathy revealed that afflicted mice develop progressive motor axonopathy, even when ALA levels are normal or only mildly increased . In addition, the findings of our previous study suggested that there is no correlation between the severity of neurological manifestations and urinary ALA and porphobilinogen levels . Frequent exposure to neurotoxicity and the accumulation of porphyrin precursors in the nervous system may be related to the severity of the neurological porphyria.…”
Section: Discussionmentioning
confidence: 59%
“…However, a PBGD‐deficient mouse model of AIP neuropathy revealed that afflicted mice develop progressive motor axonopathy, even when ALA levels are normal or only mildly increased . In addition, the findings of our previous study suggested that there is no correlation between the severity of neurological manifestations and urinary ALA and porphobilinogen levels . Frequent exposure to neurotoxicity and the accumulation of porphyrin precursors in the nervous system may be related to the severity of the neurological porphyria.…”
Section: Discussionmentioning
confidence: 59%
“…and Black et al . [15,19] described MR patterns ranging from mild ischemic area up to reversible lesions [20, 21]. Important brain perfusion defects in AIP have been recently described by SPECT by Totaro et al .…”
Section: Discussionmentioning
confidence: 99%
“…These classically present with a neurological complaint [15, 16]. Peripheral neuropathy is the most common central nervous system manifestation.…”
Section: Discussionmentioning
confidence: 99%